2010
DOI: 10.1007/s10006-010-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ibuprofen versus lornoxicam after third molar surgery: a randomized, double-blind, crossover pilot study

Abstract: Ibuprofen 400 mg and lornoxicam 8 mg were rated as equal and effective pain treatment medication after wisdom tooth surgery. In comparison, neither of the drugs provided clinical advantages nor did side effects occur more frequently after one of the analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In a study comparing the efficacy of ibuprofen versus lornoxicam after third molar surgery, it was reported that effective pain relief was provided and there was no significant difference between the groups [29] . The concentration of prostaglandins in acutely injured tissue reaches its maximum level at 3 or 4 h after injury with the result of a peak intensity of postoperative pain [29] . Seventy-five percent of the VASR scores at 4 and 8 h were lower than 50 mm for all of the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing the efficacy of ibuprofen versus lornoxicam after third molar surgery, it was reported that effective pain relief was provided and there was no significant difference between the groups [29] . The concentration of prostaglandins in acutely injured tissue reaches its maximum level at 3 or 4 h after injury with the result of a peak intensity of postoperative pain [29] . Seventy-five percent of the VASR scores at 4 and 8 h were lower than 50 mm for all of the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lustenberg et al [22] compared the analgesic efficacy and tolerability of a pre-emptive/post-surgical 4-day regimen of oral ibuprofen (400mg) with that of Lornoxicam (8mg) and concluded that both drugs were equally effective in managing pain after third-molar extraction.…”
Section: Discussionmentioning
confidence: 99%
“…It is as effective as other NSAIDs in relieving pain of osteoarthritis, rheumatoid arthritis, ankylosing spondylitis, acute sciatica and low backache. In one randomized controlled trial (RCT), ibuprofen and lornoxicam were similar in terms of pain intensity scores starting from 2 h to 4th day of post surgical dental extraction as well as number and severity of AEs [8]. The efficacy and tolerability of lornoxicam were equivalent to diclofenac and higher than placebo based on pain intensity difference and total area under pain relief scores in the treatment of acute sciatica/ lumbo-sciatica [20].…”
Section: Commentsmentioning
confidence: 99%
“…All NSAIDs have been associated with gastrointestinal adverse effects (AEs) such as nausea, dyspepsia, peptic ulcer, and diarrhea. Ibuprofen is the first NSAID to be approved for over-the-counter (OTC) use [8]. It is widely used for mild to moderate type of acute pain (e.g.…”
mentioning
confidence: 99%